Analysis of albumen gland proteins suggests survival strategies of developing embryos of Pomacea canaliculata. (3rd April 2018) - Xiong, Ya-Ming; Yan, Zhi-Hui; Zhang, Jia-En; Li, Hai-Yun
ABSTRACT: The albumen gland of Pomacea canaliculata secretes the perivitelline fluid (PVF) surrounding the developing embryo which gives its eggs a highly effective defence against environmental factors and predators. Although previous studies have determined the functions of some PVF proteins extracted from P. canaliculata eggs, knowledge of the protein composition of PVF is still limited. In this study we use LC-MS/MS to identify 87 proteins from the albumen gland of P. canaliculata, 53 of which (60.9%) were annotated using the KEGG database. These classified into five functional groups: metabolism (54.7%); genetic information processing (9.4%); environmental information processing (3.8%); cellular processes (11.3%); and organismal systems (20.8%). The analyses found 12 proteins related to innate immunity and three proteins linked to defence against predation, providing important information for studies on embryo survival strategies and the invasive capabilities of P. canaliculata.